Isocitrate dehydrogenase, lactate dehydrogenase and Î±-glycerophosphate dehydrogenase polymorphysm enzyme of Black Tiger Shrimp (Penaeus monodon Fab.) which is hydrogen sulfide resistant - OKID PARAMA ASTIRIN; SUTIMAN BAMBANG SUMITRO (Biodiversitas Journal of Biological Diversity, 2006)
The hydrogen sulfide is one of compound which very often found in the shrimp pond caused by anaerobic decomposition or as a natural condition of the sea water which have volcano activity. This research was obtaining information of the differences of genetic expression between black tiger shrimp which could resist to H2S and the one which could not survive in this H2S. This research also trying to obtain information the genetic variety which could resist to H2S. The genetic variety of black tiger shrimp which could resist to H2S has been analysis with allozyme electrophoresis technique, using specific tissue meat and buffer CAPM (Citric Acid Aminopolimorpholine) pH 6.From the three enzymes analyzed it could be detected that IDH enzyme (Isocitrate dehydrogenase) has locus polymorphic, whereas enzyme Î±-GDP (Î±-glycerophosphate dehydrogenase) and LDH (lactate dehydrogenase) with monomorphic locus. The average heterozygosity for the group which could resist to H2S is 0.070, whereas the group which could not survive in the H2S is 0.042. The control group has heterozygosity 0.041. The group which could resist to H2S with higher heterozygosity will have bigger chance to survive and have better adaptation ability in environmental changes. A high heterozygosity made possible for genetic population improvement by exploiting the good gene.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Penaeus monodon Fab., H2S, isocitrate dehydrogenase, lactate dehydrogenase, Î±-glycerophosphate dehydrogenase, allozyme